Airbag models for aircraft passenger seats. Issue 6 (2nd November 2021) - Chiba, Masakatsu; Shimizu, Kohei; Yasui, Takuya; Katayama, Kazuo; Yamano, Akio; Yutani, Hiroshi
Abstract: Two analytical models are presented for an airbag installed as an aircraft seat cushion to reduce shock to passengers during an emergency. In the first model, an airbag is modelled as a rigid cylinder, while in the second model, initial deformed shapes and volume changes of an airbag after crash are considered. In numerical simulations, effects of orifice contraction coefficient, exhaust diameter ratio and rupture pressure on the inner pressure of the airbag, and acceleration and displacement of the falling body are clarified for the two models by dropping a falling mass against a pre-inflated test airbag equipped with an exhaust orifice. Furthermore, the numerical results are compared with experimental results.